Human Resource Management Practices Assessing Added Value - Andresen, Maike; Nowak, Christian; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
This book is designed to help practitioners and academics to assess the added value of HR practices. It provides hands-on recommendations for choosing effective means to manage HR and specific suggestions aimed at facilitating the measurement of HR practices$1 (Bimpact on value creation. Evidence-based recommendations are made by drawing on thorough empirical research from various research traditions and academic disciplines. It covers a wide variety of tasks faced by the HR function and specifically addresses new challenges such as assessing the added value of work-life balance practices.s
Assessing the Added Value of Human Resource Management Practices -- Adding Value and HRM Practice -- Realizing the Highest Value of Investments in Talent Management -- How to Evaluate Employer Brands -- Assessing the Return on Investments in Human Resource Development -- The Added Value Expatriation -- A Look into the Future: Is Working Time Freedom Apt to Add Value for Different Stakeholders? - Creating Value Through Occupational Health Management -- Investments in Work-Life Balance Pay Off -- Investing in the Subjective Well-Being of Temporary Workers -- Added Value of Employee Financial Participation -- Does Employee Downsizing Really Work? - Determining Outcomes of HRM Practices.
Keywords: Economics; Business planning; Applied psychology; Economics/Management Science; Human Resource Management; Organization/Planning.; Industrial, Organisational and Economic Psychology